2015
DOI: 10.1111/ijd.12730
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma of the lower extremities: foot site is an independent risk factor for clinical outcome

Abstract: Foot melanoma could represent a particular subgroup, which could require specific management in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 22 publications
8
17
0
1
Order By: Relevance
“…According to several molecular studies, genetic alterations in the number of copies of DNA and mutation rates of BRAF, N‐RAS, and KIT differed between AM and melanoma at other sites . In addition, several clinical studies have demonstrated a higher risk for local recurrence and a worse prognosis of AM compared to other melanomas . Accordingly, thoughtful consideration on surgical management of AM is required especially with regard to optimal excision margin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several molecular studies, genetic alterations in the number of copies of DNA and mutation rates of BRAF, N‐RAS, and KIT differed between AM and melanoma at other sites . In addition, several clinical studies have demonstrated a higher risk for local recurrence and a worse prognosis of AM compared to other melanomas . Accordingly, thoughtful consideration on surgical management of AM is required especially with regard to optimal excision margin.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma of acral locations, including the hands and feet, occurs very rarely in the Caucasian; however, it is the most common cutaneous melanoma in the nonwhite population . Acral melanoma (AM) has been known to confer a worse prognosis than melanoma at other anatomic sites , which was thought to result from a delayed diagnosis and the advanced stage at presentation. However, recent large cohort studies have demonstrated that AM shows poorer oncological outcomes even after adjusting for prognostic factors, such as staging, suggesting that it may be more biologically aggressive .…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference in mortality was observed between group A and group B. Many studies conducted in Western countries [ 10 15 16 ] have asserted that melanoma of the foot occupies a large portion of tissue and that aggressive resection is necessary due to frequent local and regional recurrence. A poor prognosis compared to melanoma of other parts of the body has also been reported.…”
Section: Discussionmentioning
confidence: 94%
“…Many parameters have previously been analysed to find out new prognostic parameters for melanoma patients. Age at diagnosis, primary cutaneous tumour site and number of lymphatic basin drainage have been proposed even if they have not been included yet in the AJCC classification (Balch et al , 2013; Pasquali et al , 2014; Sanlorenzo et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Histological regression in primary cutaneous melanoma occurs in 10–35% of cases (Blessing et al , 1990; Sanlorenzo et al , 2015). In our series, regression was found in 16% of stage III melanoma patients.…”
Section: Discussionmentioning
confidence: 99%